Keberlanjutan UMKM di Jawa Barat di Tinjau Dari New-era Business : Transformasi Digital, Dividen Digital, dan Kewirausahaan - Machin; Muhammad Reza Aulia; Joni Hendra; Elvina Safitri; Adhi Bawono (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
This study examines the sustainability of micro, small, and medium enterprises (MSMEs) in West Java and the role of digital transformation, digital dividends, and entrepreneurship in promoting their sustainability. The research employs a mixed methods approach, including surveys, semi-structured interviews, and literature reviews. The survey results indicate that financial access, market access, government policies and regulations, and human resources are important factors influencing the sustainability of MSMEs in West Java. Digital transformation and entrepreneurship are found to play a significant role in driving sustainability by enabling MSMEs to streamline their operations, access new markets, and adapt to ever-changing market conditions. Digital dividends are also identified as important contributors to sustainability by creating new jobs and contributing to inclusive economic growth. This study has important implications for policymakers, as well as MSME owners and managers in West Java, as it provides insights into how to promote long-term sustainability of MSMEs in the region.